2009
DOI: 10.1080/03079450903183652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a liveMycoplasma synoviaevaccine on the production of eggshell apex abnormalities induced by aM. synoviaeinfection preceded by an infection with infectious bronchitis virus D1466

Abstract: An experimental study was conducted to assess the effect of a live Mycoplasma synoviae vaccine (Vaxsafe † MS; Bioproperties Pty Ltd, Ringwood, Victoria, Australia) on M. synoviae-induced eggshell apex abnormalities (EAA). Four experimental groups of specified-pathogen-free white laying hens were made. All groups were inoculated with infectious bronchitis virus D1466 at 18 weeks of age. One group did not receive further treatment (non-vaccinated non-challenged (NVNC)). Two groups were vaccinated at 14 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Sequencing of the vlhA gene of the first M. synoviae isolate able to induce EAA showed a 12 bp insertion (Feberwee et al, 2009b). Results from the present study and comparisons with sequences from Genbank demonstrated that this 12 bp insertion is not unique to EAA isolates, but is also found in isolates obtained from inflamed joints.…”
Section: Discussionmentioning
confidence: 55%
“…Sequencing of the vlhA gene of the first M. synoviae isolate able to induce EAA showed a 12 bp insertion (Feberwee et al, 2009b). Results from the present study and comparisons with sequences from Genbank demonstrated that this 12 bp insertion is not unique to EAA isolates, but is also found in isolates obtained from inflamed joints.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies reported EAA incidence of 1.3% in an intensive layer farm in Italy (Catania et al, 2010), 25% in layers housed on the floor in The Netherlands (Feberwee et al, 2009b) and 22.9% in challenged SPF layers (Feberwee et al, 2009a).…”
Section: Resultsmentioning
confidence: 99%
“…A MS strain was isolated from the oviduct of hens producing eggs with EAA and yielded the same abnormalities after experimental infection (Feberwee et al, 2009b). It was also shown that antibiotic treatment and vaccination against MS reduced the incidence of EAA (Feberwee et al, 2009a;Feberwee et al, 2009b;Catania et al, 2010). Nevertheless, despite these very distinctive characteristics, EAA may not be necessarily pathognomonic of infections by any specific pathogen (Strugnell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The param eter th at had the most variation was eggshell thickness a t the apex; hence, it can be inferred th a t the lower eggshell strength was mostly related to the lower eggshell thick ness at the apex. Feberwee et al (2009a) also observed a reduction of 32.34 to 34.86% in the eggshell strength of EAA eggs from hens experimentally infected with M. synoviae. It should be highlighted th a t normal eggs from hens infected with M. synoviae are also affected and also have a lower eggshell strength (Feberwee et al, 2009a;Gole et al, 2012;Silva et al, 2012).…”
Section: Egg Quality Analysismentioning
confidence: 61%